The Effect of Work Flexibility and Job Satisfaction on Job Performance Among Live Streaming Hosts at Agency X - Natasya Inka Pramesti; Pras Rendy (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Flexible working arrangements do not always have a positive impact on performance; they can also create performance pressure that affects job performance. This condition triggers stress, especially when the achievements at the start of the live streaming session are still far from the set targets. This study aims to measure the effects of work flexibility and job satisfaction on job performance among live streaming hosts at Agency X. It uses a total population sampling method, with a sample size equal to the population of 60 live streaming hosts. The research method uses a quantitative, correlational design. The results of the study indicate that work flexibility and job satisfaction simultaneously have a significant effect on job performance (F = 46.470; p < 0.001), with a coefficient of determination (R²) of 0.620 indicating that 62% of the variation in job performance can be explained by the two independent variables work flexibility and job satisfaction while the remaining 38% is influenced by other factors outside the scope of the variables under study. The analysis results partially show that work flexibility has a positive and significant effect on job performance (β = 0.570; t = 6.129; p < 0.001). This finding indicates that the greater an individual's perceived work flexibility, the higher their job performance. Conversely, job satisfaction exhibits a negative and significant influence on job performance (β = -0.881; t = -9.469; p < 0.001). These results indicate that higher job satisfaction is negatively correlated with job performance in this study. Given these significant effects, it follows that changes in the level of work flexibility or job satisfaction will be accompanied by changes in job performance.